Odyssey of dwelling : challenge of modern architecture - Salihu, Astrit (Array, 2019)
The main focus of this article is on philosophical and architectural problems of dwelling. At these junctures, a great debate is again incited regarding the alleged problems in parallel with challenging the standpoints that led to a deadlock which was caused by a modern discourse. A referential figure re-thinking the dwelling outside the framework of modernity is a Norwegian architect and architectural theorist Christian Norberg-Schulz. Inspired by phenomenologists Martin Heidegger and Maurice Merleau-Ponty, Norberg-Schulz will strive to achieve a coherent argument regarding the inseparable link between existence and space; in other words, to settle down an argument about the existential roots of the architectonical space. This premise contests entirely the indifference and arbitrariness of modern architects who remain prone to neglect the fundamental segment of human spatial existence in their works. Having delved deeply into the question of existential and architectonical space and asserting a close connection between the two, Norberg-Schulz developed a widely discussed conception in recent years: the concept of genius loci. By this approach, finally, the self-maintaining discourse of modernity is discarded. The relevance of context, eclectic and recovering of that which is traditional will return from the zero-level of denying the tradition. In this way, the concept of genius loci seems to be highly useful in plain and different architectural definitions, which seem to challenge our existence perpetually. This paper will try to explicate the theoretical consequences on the problems of dwelling, as an essential axis of our Being.